The effects of different feed-grade antibiotics on growth performance of weanling pigs in a research environment - Gottlob, R.O.; Hastad, C.W.; Groesbeck, C.N.; Lawrence, K.R.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 168 weanling pigs (initially 13.8 lb and 21 ± 3 d of age, PIC) were used to determine the effects of different feed-grade antibiotics on nursery-pig performance. Pigs were fed one of four experimental diets: control with no antibiotics; or the control diet with added Denagard/CTC (35 g/ton Denagard™, 400 g/ton Chlortetracycline); Neo-Terramycin® (140 g/ton Neomycin Sulfate, 140 g/ton Oxytetracycline HCl); or Mecadox® (Carbadox, 50 g/ton). Overall (d 0 to 28 after weaning), pigs fed diets containing Denagard/ CTC or Neo-Terramycin® had greater ADG and ADFI (P<0.05) than did pigs fed all other diets, and had improved F/G (P<0.05), compared with that of pigs fed the control diet. Also, pigs fed diets containing Mecadox® had improved ADG and F/G (P<0.05) compared with those of pigs fed the control diet. The addition of feed-grade antibiotics in swine diets resulted in improved growth performance, and pigs fed Denagard/CTC or Neo-Terramycin® had the greatest improvement in growth performance.
Keywords: Swine; Nursery pigs; Antibiotics; Growth; Pigs